Activity Test Of Papaya Fruit Extract And Curcuma Mangga As An Appetite Enhancer With Anorexia Test Model On Marshmallow Preparation Innovation - Ridwan Mu'zizat; Rival Rizki Hadiansyah Saputra; Rizqi Indra Hartanto; Rifki Budiansyah; Zulkaida; Fauzia Ningrum Syaputri (Jurnal Riset Kefarmasian Indonesia, 2026)
Feeding difficulties in children are becoming an increasing global problem. Natural alternatives such as Carica papaya and Curcuma mangga are believed to increase appetite. This study tested the combination of the two as an anorexia agent in the form of marshmallows, as an attractive, nutritious, and attractive delivery innovation for active substances that children like. The study used a combination of Carica papaya and Curcuma mangga extracts in marshmallow form to treat anorexia. The process includes extraction, phytochemical testing, rat testing, marshmallow formulation, and organoleptic evaluation, weight uniformity, and hedonic test for children and adults to assess its effectiveness and acceptability. Phytochemical screening showed Carica papaya and Curcuma mangga extracts contained alkaloids, steroids, polyphenols, and vitamin C. The anorexia test had a p-value of 0.05. The anorexia test has a p value (>0.05) so it has an insignificant value, but the extract still increases appetite. The formulated marshmallow has a chewy texture, a favorable aroma, but the taste and texture are less attractive to panelists. Carica papaya and Curcuma mangga extracts contain active compounds and showed appetite- enhancing effects although not statistically significant. Marshmallow has a vanilla aroma that is preferred, but the taste and shape are less than optimal. The study is limited in number of samples, further quantitative analysis and formulation evaluation are recommended.